The Strategic Role of MSMEs in Accessing Working Capital Financing Through Islamic Banks in Berau Regency - Saputra, Handayani Jaka; Syarifuddin, Syarifuddin; Suciatno, Suryadi (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2025)
Micro, small, and medium-sized businesses, or MSMEs, are vital to the economy. Many MSME businesses find it difficult to secure the funding they need to keep running. However, there are currently very few MSME players in Islamic banking that have access to capital. The purpose of this study is to investigate how MSME actors' readiness to take business loans from Islamic banks is influenced by many characteristics, including promotion, product knowledge, income, region, and education. The approach used is quantitative research. For this investigation, the sample consisted of 125 respondents.  The study technique makes use of logistic regression. The results showed a strong positive correlation between the income, promotion, and product competence of MSME players at Islamic banks in Berau Regency and their willingness in implementing KUR. The inclination of MSME operators in the Berau Regency to accept KUR at Islamic banks is not greatly influenced by factors such as income or location. The study's conclusions indicate that for intense socializing, there will be a stronger focus on print, technology, and interpersonal media. It is envisaged that this project would provide the general public with a comprehensive grasp of the Islamic banking system and its products, as they are not familiar with Islamic banking. This would incentivize Bank Syariah Indonesia's existing and prospective customers, especially MSME operators in the Berau Regency, to utilize KUR (People's Business Credit) products.